Serum Levels of Oxidative Stress Markers in Patients with Type 2 Diabetes Mellitus and Non-alcoholic Steatohepatitis - Casoinic F.; Sampelean D.; Buzoianu Anca D.; Hancu N.; Baston Dorina (Sciendo, 2016)
Introduction. Oxidative stress is one of the key mechanisms responsible for disease progression in non-alcoholic fatty liver disease. The aim of this study was to evaluate the serum levels of oxidative stress markers in patients with type 2 diabetes mellitus (DMT2) and non-alcoholic steatohepatitis (NASH) and test their relationships with clinical and biochemical patient characteristics, compared to patients with DMT2 without non-alcoholic fatty liver disease (NAFLD), and controls.